An electrolyte additive and its application, electrolyte and aqueous zinc ion battery
By adding 1-alkyl-3-metronazole yang ions and anionic electrolyte additives to the electrolytes of zinc ion batteries, the problem of uneven deposition of zinc branch crystals is solved, and the uniform deposition and battery life of zinc ions and battery life are realized. Significant extension.
Patent Information
- Application Number
- CN202210745644.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-06-28
AI Technical Summary
Zinc ion batteries have problems with uneven deposition of zinc dendrites in large-scale industrial applications, resulting in short circuits and premature battery failure. Existing additives are costly or have many side reactions, making it difficult to effectively inhibit the growth of dendrites.
A electrolyte additive, which is [xmim] Y, of which [XMIM] is 1-alkyl-3-methylmirazole yang ion, and Y is anion. This additive is adsorbed on the surface of the zinc negative surface, the flat surface is flat, and when the zinc ion is deposited, it has the effect of "cutting -edge shielding", which inhibits the generation and growth of the chinetic crystal.
The uniform sedimentation of zinc ions is achieved, significantly reduced the formation of zinc branches, and extended the life of the zinc ion battery of the water system, nearly 15 times, and low cost and high efficiency.
Smart Images

Figure CN114927772B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to electrolytes, and more specifically, relates to an electrolyte additive and application thereof, an electrolyte and an aqueous zinc ion battery. Background Art
[0002] With the increasing depletion of fossil fuels and the increasingly serious environmental problems, the development of sustainable new energy has attracted widespread attention. People are in urgent need of developing an efficient, safe, low-cost and environmentally friendly energy storage device. Among them, lithium-ion batteries have been widely used due to their high energy density and good cycle stability. However, the high cost of lithium resources and the safety issues of electrolytes limit the application of lithium-ion batteries in the field of large-scale energy storage.
[0003] In contrast, zinc is low-cost and non-toxic. The safety of zinc-ion batteries is greatly improved when used with aqueous electrolytes. In addition, zinc metal has good stability in alkaline, neutral and weakly acidic aqueous solutions. Therefore, zinc-ion batteries are expected to become the most promising new energy storage device. However, there are still many challenges in the large-scale industrial application of zinc-ion batteries. First, the uneven deposition of zinc ions often forms dendrites, which will pierce the diaphragm and cause a short circuit. Second, zinc-ion batteries have many side reactions, and their interfacial parasitic reactions include hydrogen evolution corrosion and surface passivation, which lead to low electrode coulomb efficiency, low zinc utilization, and premature battery failure.
[0004] Among them, in order to solve the problem of zinc dendrites, researchers have made a lot of attempts. Some studies are committed to regulating the original morphology of zinc negative electrode, such as preparing zinc negative electrode by rolling process or heat treatment process, and some studies are designed and modified to homogenize the deposition of zinc ions. The above methods often have complicated preparation processes, which will increase the cost a lot while improving the performance. In contrast, the design of electrolyte additives can improve many problems by adjusting the composition and structure of the electrolyte or performing interface regulation, which is the simplest and most economical strategy. So far, electrolyte additives are mainly divided into polymer additives and metal ion additives. Both additives can be adsorbed on the surface of zinc negative electrode and inhibit the growth of dendrites by homogenizing the deposition of zinc ions, but the adsorption and binding force of polymer additives is weak, and metal ions are expensive and easy to cause various side reactions. In addition, there are some additives that can inhibit dendrite growth by optimizing the solvation structure of the electrolyte, but such additives are used in large amounts and have high costs. Therefore, it is urgent to find a new additive that can play a good role in inhibiting the growth of zinc dendrites when adding a small amount of additives. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides an electrolyte additive and its application, an electrolyte and an aqueous zinc ion battery, which make the deposition of zinc ions more uniform and inhibit the formation and growth of zinc dendrites.
[0006] To achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided an electrolyte additive, the electrolyte additive is expressed as: [XMIM]Y, wherein [XMIM] is a 1-alkyl-3-methylimidazolium cation, the alkyl group is one or a combination of ethyl, butyl, hexyl or octyl, and Y is an anion.
[0007] Preferably, the anion is one or a combination of chloride ion, tetrafluoroborate ion, hydrogen sulfate ion or trifluoromethanesulfonate ion.
[0008] Preferably, the additive is 1-butyl-3-methylimidazolium trifluoromethanesulfonate.
[0009] According to another aspect of the present invention, there is provided an electrolyte comprising a zinc salt, water and the above-mentioned additive.
[0010] Preferably, the concentration of the additive in the electrolyte is 0.0002M to 0.08M.
[0011] Preferably, the concentration of the additive in the electrolyte is 0.02M to 0.04M.
[0012] Preferably, the concentration of the zinc salt in the electrolyte is 2M.
[0013] Preferably, the zinc salt includes one or a combination of zinc sulfate, zinc nitrate, zinc acetate and zinc chloride.
[0014] The third aspect of the present application provides an aqueous zinc ion battery containing the above-mentioned electrolyte.
[0015] In a fourth aspect, the present application provides an application of the above-mentioned electrolyte additive, wherein the additive is used in the electrolyte of an aqueous zinc ion battery.
[0016] In general, compared with the prior art, the above technical solutions conceived by the present invention provide an electrolyte additive and its application, electrolyte and aqueous zinc ion battery with the following beneficial effects:
[0017] 1. The additive of the present application, [XMIM], as a long-chain cation, contains N groups that can be adsorbed on the surface of the zinc negative electrode, which has the effect of leveling the negative electrode surface. At the same time, it can also play a "tip shielding" effect when zinc ions are deposited, making the deposition of zinc ions more uniform, thereby inhibiting the formation of zinc dendrites.
[0018] 2. Among the anions, hydrogen sulfate is acidic after hydrolysis, while chloride, tetrafluoroborate and trifluoromethanesulfonate are neutral after hydrolysis. Chloride is cheaper. Both tetrafluoroborate and trifluoromethanesulfonate have good effects on inhibiting the growth of zinc dendrites. When combined with [XMIM] cations, they can better inhibit the growth of zinc dendrites.
[0019] 3. When the present invention is used as an additive to the electrolyte, only a small amount is needed to effectively suppress zinc dendrites, with low cost and high efficiency.
[0020] 4. The additives in this application can significantly reduce the formation of zinc dendrites and increase the life of aqueous zinc ion batteries by nearly 15 times, with significant effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The zinc-zinc symmetric battery of Example 1 and Comparative Example 1 at 2 mA cm -2 , 1mAh cm -2 Cycle life test diagram under conditions.
[0022] Figure 2 The zinc-zinc symmetric battery of Example 1 and Comparative Example 1 at 5 mA cm -2 , 5mAh cm -2 Cycle life test diagram under conditions.
[0023] Figure 3 The zinc-zinc symmetric battery of Example 1 is at 5 mA cm -2 , 5mAh cm -2 Morphology of zinc deposition after 10 cycles under the same conditions.
[0024] Figure 4 The zinc-zinc symmetric battery of Comparative Example 1 was -2 , 5mAh cm -2 Morphology of zinc deposition after 10 cycles under the same conditions.
[0025] Figure 5 The zinc-zinc symmetric battery of Example 2 and Comparative Example 2 at 1 mA cm -2 , 1mAh cm -2 Cycle life test diagram under conditions.
[0026] Figure 6 The zinc-zinc symmetric battery of Example 3 and Comparative Example 3 at 10 mA cm -2 , 10mAh cm -2 Cycle life test diagram under conditions.
[0027] Figure 7This is a test chart of the cycle life of the zinc-manganese dioxide full battery of Example 4 and Comparative Example 4 under 0.5C conditions.
[0028] Figure 8 The zinc-zinc symmetric battery of Example 5 is at 1 mA cm -2 , 1mAh cm -2 Cycle life test diagram under conditions.
[0029] Fig. 9 The zinc-zinc symmetric battery of Example 6 and Comparative Example 6 at 10 mA cm -2 , 10mAh cm -2 Cycle life test diagram under conditions.
[0030] Fig.10 The zinc-zinc symmetric battery of Example 6 is at 5 mA cm- 2 , 5mAh cm -2 Morphology of zinc deposition after 10 cycles under the same conditions.
[0031] Fig.11 The zinc-zinc symmetric battery of Comparative Example 6 was -2 , 5mAh cm- 2 Morphology of zinc deposition after 10 cycles under the same conditions.
[0032] Fig.12 The zinc-zinc symmetric battery of Example 7 and Comparative Example 7 at 5 mA cm -2 , 5mAh cm -2 Cycle life test diagram under conditions. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] See also Figure 1 and Figure 2 In a first aspect, the present invention provides an electrolyte additive, the additive is expressed as [XMIM]Y, wherein [XMIM] is a 1-alkyl-3-methylimidazolium cation, the alkyl group is one or a combination of ethyl, butyl, hexyl or octyl, and Y is an anion.
[0035] In a further preferred embodiment, the anion is one or a combination of chloride ion, tetrafluoroborate ion, hydrogen sulfate ion or trifluoromethanesulfonate ion.
[0036] In another aspect, the present application provides an electrolyte, comprising zinc salt, water and an additive of the electrolyte, wherein the concentration of the additive in the electrolyte is 0.0002M to 0.08M.
[0037] The zinc salt includes one or a combination of zinc sulfate, zinc nitrate, zinc acetate, and zinc chloride. It is not limited to zinc sulfate, zinc nitrate, zinc acetate, and zinc chloride, and any zinc salt that can hydrolyze zinc ions after hydrolysis can be used.
[0038] The concentration of the zinc salt in the electrolyte is 2M.
[0039] On the other hand, the present application provides an aqueous zinc ion battery containing the above electrolyte. Therefore, the aqueous zinc ion battery includes the above additive, and the [XMIM] in the additive is a long-chain cation, and the N group contained in it can be adsorbed on the surface of the zinc negative electrode, which has the effect of leveling the negative electrode surface, and can also play a "tip shielding" effect when zinc ions are deposited, so that the deposition of zinc ions is more uniform and the growth of zinc dendrites is avoided; among the anions, hydrogen sulfate is acidic after hydrolysis, and chloride ions, tetrafluoroborate ions and trifluoromethanesulfonate ions are neutral after hydrolysis, and chloride ions are relatively cheap. Both tetrafluoroborate ions and trifluoromethanesulfonate ions have a good effect on inhibiting the growth of zinc dendrites.
[0040] On the other hand, the present application provides an application of the above-mentioned electrolyte additive, which is used in the electrolyte of an existing aqueous zinc ion battery and can effectively inhibit the formation and growth of zinc dendrites.
[0041] Embodiment 1:
[0042] The additive used in this example is 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4).
[0043] [BMIM]BF4 and zinc sulfate heptahydrate (ZnSO4·7H2O) were added to deionized water to prepare a 2M ZnSO4 aqueous solution containing 0.02M [BMIM]BF4 as the electrolyte. Metal zinc was used as the electrode and glass fiber was used as the separator to assemble a button cell to test the performance of the zinc-zinc symmetric battery. Two conditions were selected for the symmetric battery test, namely 2mA cm -2 , 1mAhcm -2 and 5 mA cm -2 , 5mAh cm -2 At 2 mA cm -2 , 1mAh cm -2 The performance of the battery under the conditions Figure 1 As shown, its cycle life reaches more than 3000 hours; and 5mA cm -2, 5mAh cm -2 The performance of the battery under the conditions Figure 2 As shown in Figure 2, its cycle life reaches 387 hours, and by observing the electrode at 5mA cm -2 , 5mAh cm -2 The morphology after 10 cycles under the same conditions shows that the zinc grows uniformly and densely, and the overall surface is flat, and the risk of dendrite formation is low. Figure 3 shown.
[0044] Comparative Example 1: (without [BMIM]BF4)
[0045] Zinc sulfate heptahydrate (ZnSO4·7H2O) was added to deionized water to prepare a 2M ZnSO4 aqueous solution as the electrolyte. Metal zinc was used as the electrode and glass fiber was used as the separator to assemble a button cell for the performance test of the symmetrical cell. The test conditions were also selected as 2 mA cm -2 , 1mAh cm -2 and 5 mA cm -2 , 5mAh cm -2 At 2 mA cm -2 , 1mAh cm -2 The performance of the battery under the conditions Figure 1 As shown, its cycle life is only 90 hours; and 5mA cm -2 , 5mAh cm -2 The performance of the battery under the conditions Figure 2 As shown in the figure, its cycle life is only 80 hours. Similarly, the electrode is observed at 5mA cm -2 , 5mAh cm -2 The morphology after 10 cycles under the same conditions showed that the growth of zinc was disorderly and uneven, and there was a risk of dendrite formation, such as Figure 4 shown.
[0046] Embodiment 2:
[0047] The additive used in this example is 1-butyl-3-methylimidazole hydrogen sulfate ([BMIM]HSO4).
[0048] [BMIM]HSO4 and zinc sulfate heptahydrate (ZnSO4·7H2O) were added to deionized water to prepare a 2M ZnSO4 aqueous solution containing 0.0002M [BMIM]HSO4 as the electrolyte. Button cells were assembled as in Example 1 and the symmetrical cell performance was tested at 1 mA cm -2 , 1mAh cm -2 The test results are as follows: Figure 5 As shown, its cycle life reaches 742 hours.
[0049] Comparative Example 2: (without [BMIM]HSO4)
[0050] The electrolyte composition of Comparative Example 2 is the same as that of Comparative Example 1, that is, 2M ZnSO4 aqueous solution is used as the electrolyte, and the button cell is assembled at 1 mA cm -2 , 1mAh cm -2 Symmetrical battery performance test was carried out under the following conditions. The test results are as follows: Figure 5 As shown, its cycle life is only about 225 hours.
[0051] Embodiment 3:
[0052] The additive used in this embodiment is 1-butyl-3-methylimidazolium trifluoromethanesulfonate (BMIMOTF).
[0053] [BMIM]OTF and zinc sulfate heptahydrate (ZnSO4·7H2O) were added to deionized water to prepare a 2M ZnSO4 aqueous solution containing 0.004M [BMIM]OTF as the electrolyte. A symmetrical battery was assembled in the manner of Example 1 for performance testing. The test condition was 10 mA cm -2 , 10mAh cm -2 , the test results are as follows Figure 6 As shown, its cycle life reaches 244 hours.
[0054] Comparative Example 3: (without [BMIM]OTF)
[0055] The electrolyte composition of Comparative Example 3 is the same as that of Comparative Example 1, using 2M ZnSO4 aqueous solution as the electrolyte, at 10 mA cm -2 , 10mAh cm -2 The cycle life of its symmetrical battery is only about 65 hours under such conditions. Figure 6 shown.
[0056] Embodiment 4:
[0057] The additive used in this example is 1-butyl-3-methylimidazolium chloride ([BMIM]CL).
[0058] [BMIM]CL, zinc sulfate heptahydrate (ZnSO4·7H2O) and deionized water were prepared into a 2M ZnSO4 aqueous solution containing 0.004M [BMIM]CL as the electrolyte, metallic zinc was used as the negative electrode, glass fiber was used as the separator, and MnO2 was loaded onto a stainless steel mesh as the positive electrode to assemble a button cell for full battery performance testing. The surface loading of MnO2 in the positive electrode was 3mg cm -2 , the test condition is 0.5C. Its performance is as follows Figure 7As shown, the full cell with 0.004M [BMIM]CL added can maintain a relatively stable capacity over 150 cycles.
[0059] Comparative Example 4: (without [BMIM]CL)
[0060] A 2M ZnSO4 aqueous solution was used as the electrolyte and a full cell was assembled in the manner of Example 4. The surface loading of MnO2 at the positive electrode was 3 mg cm -2 The test conditions are also 0.5C. Figure 7 As shown, it can be seen that without the additive, the full battery short-circuited at only around 54 cycles.
[0061] Embodiment 5:
[0062] In order to compare the effects of different chain lengths of cations, this embodiment selects [OMIM], [HMIM], [BMIM] and [EMIM] of different chain lengths as cations, and respectively uses chloride ions as additives, and the concentration is set to 0.02 M. That is, a 2M ZnSO4 aqueous solution containing 0.02M [OMIM]CL, a 2M ZnSO4 aqueous solution containing 0.02M [HMIM]CL, a 2M ZnSO4 aqueous solution containing 0.02M [BMIM]CL and a 2M ZnSO4 aqueous solution containing 0.02M [EMIM]CL are respectively configured as electrolytes, and symmetrical cells are assembled in the manner of Example 1 for performance testing, and the test conditions are selected to be 1 mA cm -2 , 1mAh cm -2 , the test results are as follows Figure 8 Among the additives, [OMIM] has the longest chain length, followed by [HMIM], then [BMIM], and the shortest chain length is [EMIM]. Figure 8 The results show that the battery life containing 0.02M[EMIM]CL is about 420 hours, the battery life containing 0.02M[BMIM]CL is about 600 hours, the battery life containing 0.02M[HMIM]CL is about 660 hours, and the battery life containing 0.02M[OMIM]CL is about 500 hours. From this result, it can be inferred that as the length of the cation chain increases, the better the adsorption effect, the more obvious the improvement in battery performance; but too long a chain length will reduce the cycle life of the battery, which may be related to the effect of the chain length on the distribution of the electron cloud. Too long a chain length reduces the overall stability of the battery. However, compared with the battery system without additives (Comparative Example 2), the cycle life of all samples in this embodiment has been improved.
[0063] Embodiment 6:
[0064] The additive used in this example is 1-butyl-3-methylimidazolium trifluoromethanesulfonate ([BMIM]OTF).
[0065] Different from Example 3, the concentration of [BMIM]OTF in this example is increased to 0.02M, that is, a 2M ZnSO4 aqueous solution containing 0.02M [BMIM]OTF is used as the electrolyte. Symmetrical cells are assembled in the same manner as in Example 1 for performance testing, and the test conditions are 10mA cm -2 , 10mAh cm -2 The test results are as follows: Fig. 9 As shown in Figure 2, its cycle life reaches 1000 hours. Furthermore, scanning electron microscopy was used to observe the symmetric battery containing the additive at 5 mA cm -2 , 5mAh cm -2 The surface morphology after 10 cycles under the condition of , it can be found that the exposed surface is relatively flat, and the growth of zinc is also relatively uniform and dense, such as Fig.10 shown.
[0066] Comparative Example 6: (without [BMIM]OTF)
[0067] Using 2M ZnSO4 aqueous solution as the electrolyte, a symmetrical battery was assembled in the same manner as in Example 1 for performance testing. The test conditions were the same as in Example 6, i.e., 10 mA cm -2 , 10mAh cm -2 The test results are as follows Fig. 9 As shown in Figure 2, the cycle life of the battery without additives is only about 64 hours. Scanning electron microscopy was used to observe the symmetric battery without additives at 5 mA cm -2 , 5mAh cm -2 The surface morphology after 10 cycles under the conditions of , the result is significantly different from that of Example 6, as shown in FIG. Fig.11 As shown, the zinc deposition of Comparative Example 6 is uneven and has some large protrusions, which provide conditions for the generation of zinc dendrites and increase the risk of short circuit of the battery.
[0068] Embodiment 7:
[0069] The additive used in this example is 1-butyl-3-methylimidazolium trifluoromethanesulfonate ([BMIM]OTF).
[0070] Different from Example 3, the concentration of [BMIM]OTF in this example is increased to 0.04M and 0.08M, that is, a 2M ZnSO4 aqueous solution containing 0.08M [BMIM]OTF is used as the electrolyte. Symmetrical cells are assembled in the same manner as in Example 1 for performance testing, and the test conditions are 5 mA cm -2, 5mAh cm -2 The test results are as follows: Fig.12 As shown in the figure, the cycle life of the 0.04M sample reached 1400 hours, while the cycle life of the 0.08M sample reached 330 hours. It can be seen that the higher the concentration of this type of additive is, the better. We speculate that too many additives will hinder the normal deposition of zinc ions, increase battery polarization, and weaken the interface regulation effect.
[0071] Comparative Example 7: (without [BMIM]OTF)
[0072] Using 2M ZnSO4 aqueous solution as the electrolyte, a symmetrical battery was assembled in the manner of Example 1 for performance testing. The test conditions were 5 mA cm -2 , 5mAh cm -2 The test results are as follows Fig.12 As shown in the figure, the sample without additives only cycled for 60 hours. It can be seen that both the 0.04M and 0.08M samples have a higher cycle life than the sample without additives.
[0073] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The invention comprises an additive 1-butyl-3-methylimidazole trifluoromethanesulfonate, a zinc salt and water, wherein the concentration of the additive in the electrolyte is 0.02 M to 0.04 M, and the concentration of the zinc salt in the electrolyte is 2 M.
2. The electrolyte according to claim 1, characterized in that The zinc salt includes one or a combination of zinc sulfate, zinc nitrate, zinc acetate and zinc chloride.
3. An aqueous zinc ion battery containing the electrolyte according to claim 1 or 2.
Citation Information
Patent Citations
Electrolyte and battery
CN106450509A
Aluminum air battery electrolyte and preparation method thereof
CN112751107A